Bahasa Inggris Bahasa Inggris - Amelia, Rizka (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of the digital era, public communication has undergone a major transformation such as public figures are no longer limited to formal bureaucrats, but also reaching popular figures from the entertainment world such as artists. Popularity, extensive social media networks, and the ability to build emotional closeness with the public, make celebrities ideal figures in conveying strategic government messages. One important event that reflects this shift is the appointment of Raffi Ahmad as the Special Envoy of the President of the Republic of Indonesia for the Development of the Young Generation and Arts Workers in 2024. This group of Young Generation and Arts Workers is known to have dynamic, expressive communication characteristics, and tends to be critical of formal, bureaucratic, and rigid communication styles. Raffi Ahmad's appointment has drawn various reactions, ranging from enthusiastic support to skeptical criticism. Therefore, the focus of this study, namely the communication style of Raffi Ahmad as an authoritative and popular figure, is very important to study.This research refers to the communication style theory by Hamilton, (2011) which provides a framework for the forms of communication patterns and dimensions of communication styles that are dominantly used by Raffi Ahmad in managing images and messages related to his role as special presidential envoy for the Development of Young Generation and Arts Workers. Descriptive quantitative methodology and data collection were carried out through content analysis of visual posts from the Instagram account @ukp_muda_raffiahmad which were then analyzed using Klaus Krippendorf content analysis. The results of the study show that Raffi Ahmad’s communication style is flexible and adaptive. The dominant style was used most frequently (40%), followed by the dramatic style (26.7%), friendly style (26.7%), and relaxed style (6.7%). The content topics included social issues (46.7%), politics (33.3%), and entertainment (20%). The communication patterns observed were informative (33.3%), self-image building (26.7%), calls to action and appreciation (16.7% each), and persuasion (6.7%). The visual communication strategy was supported by the use of “illustrator” gestures (43.3%) and semi-formal attire (56.7%). Findings also indicate that posts employing dramatic and relaxed communication styles tended to receive highly positive audience responses, while dominant styles in political content triggered resistance and negative comments. The study concludes that the effectiveness of public communication by non-political figures in the digital era is significantly influenced by the alignment between communication style, content topic, media format, and public perception of the figure’s role. Adapting communication styles based on empathy, participation, and emotional engagement is key to building credibility and strong connections in the digital public sphere. Keywords: Content Analysis, Public Communication Style, Instagram, Raffi Ahmad.